From Failure to Future Reconstructing Intellectual Property in Bankruptcy Law - Maruli, Johnson Sahat Maruli Tua; Eddy Damian; Bernard Nainggolan; Hulman Panjaitan; Christopher J. Johnstone (Lembaga Contrarius Indonesia, 2025)
In the context of a knowledge-based economy, intellectual property (IP) has emerged as a critical asset for business competitiveness, yet it remains inadequately recognized in Indonesia’s bankruptcy law. Trademarks, copyrights, and patents key components of IP are often excluded from the core bankruptcy estate due to legal ambiguity and the absence of standardized valuation and management procedures. This research aims to reconstruct Indonesian bankruptcy law to better integrate IP as a vital economic asset in insolvency proceedings. Utilizing a descriptive-analytical method with a juridical-normative approach, this study draws upon doctrinal sources and empirical data collected through interviews with legal practitioners and bankruptcy receivers. The findings reveal that current legal structures fail to reflect the real economic value of IP, resulting in underutilized assets and prolonged legal disputes, as exemplified by the Nyonya Meneer case. The study concludes that reform is urgently needed to incorporate IP into the bankruptcy framework, not only as an asset with immediate monetary value but also as a tool for post-bankruptcy recovery and sustainability. A revised legal framework would ensure equitable treatment for both creditors and debtors and align national insolvency policies with the evolving dynamics of global commerce and innovation.